2024
DOI: 10.3390/ph17030303
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medicinal Plants in the Process of Wound Healing: A Literature Review

Mayra Cedillo-Cortezano,
Luis Ruben Martinez-Cuevas,
Jesús A. Márquez López
et al.

Abstract: The literature on the use of medicinal plants in wound healing was comprehensively searched to obtain and assess the data. The data were procured via clinical studies that utilized medicinal plants and their compounds in vitro and in vivo for wound healing. This review collected data from electronic databases, including Google Scholar, PubMed, Science Direct, Web of Science, SciFinder, Thesis, and Scopus, using the search terms “natural products”, “wound healing”, and “natural compounds”, along with the keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…Many coumarins exhibit various biological properties, including anti-inflammatory, anti-ulcer, anti-tumor, antimicrobial, and anticoagulant activities (Anywar & Muhumuza, 2023). Cedillo-Cortezano et al (2024) reported that essential oils, flavonoids, and phenolic compounds have wound healing properties. These compounds have also been shown to offer advantageous effects due to their anti-inflammatory, antioxidant, and antibacterial properties.…”
Section: Phase Separationmentioning
confidence: 99%
“…Many coumarins exhibit various biological properties, including anti-inflammatory, anti-ulcer, anti-tumor, antimicrobial, and anticoagulant activities (Anywar & Muhumuza, 2023). Cedillo-Cortezano et al (2024) reported that essential oils, flavonoids, and phenolic compounds have wound healing properties. These compounds have also been shown to offer advantageous effects due to their anti-inflammatory, antioxidant, and antibacterial properties.…”
Section: Phase Separationmentioning
confidence: 99%
“…These compounds include flavonoids, tannins, and triterpenoids, which exhibit anti-inflammatory, antimicrobial, and antioxidant activities. These properties promote tissue regeneration, reduce infection risk, and enhance overall healing processes [5][6][7]. For instance, aloe vera contains mannose-6-phosphate, which helps stimulate fibroblast proliferation and collagen formation, hence improving the rate of wound healing [8].…”
Section: Introductionmentioning
confidence: 99%
“…About 62 families and 109 genera are used in traditional medicine for healing and treating wounds. Some plants with wound healing activity are presented in Figure [2].Amaranthus is a genus of herbaceous and annual plants, species of which are distributed throughout the world. Amaranthus is a highly nutritious multi-purpose plant, used as a cereal (superfood), medicinal, fodder, fuel and ornamental plant.…”
mentioning
confidence: 99%
“…About 62 families and 109 genera are used in traditional medicine for healing and treating wounds. Some plants with wound healing activity are presented in Figure [2].…”
mentioning
confidence: 99%